2016
DOI: 10.1093/molehr/gaw013
|View full text |Cite
|
Sign up to set email alerts
|

The loss of imprinted DNA methylation in mouse blastocysts is inflicted to a similar extent byin vitrofollicle culture and ovulation induction

Abstract: This study received funding by Strategic Research Programs-Groeiers (OZR/2014/97), IWT/TBM/110680 and by UZ Brussel Fonds Willy Gepts (WFWG 2013). There is no conflict of interest.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 47 publications
3
21
0
Order By: Relevance
“…Aggressive ovarian stimulation has effects on the patient's wellbeing, by increasing the risk of ovarian hyperstimulation syndrome (OHSS) (Delvigne, 2009;Rizk, 2009), as well as on the endometrium and the ovaries. There are studies showing an increased likelihood of embryo aneuploidy in connection with aggressive ovarian stimulation, even in patients younger than 35, including post-zygotic segregation errors and maternal segregation errors (Baart et al, 2007;Haaf et al, 2009), as well as having a negative impact on the maintenance of genomic imprints during early embryogenesis (Denomme and Mann, 2012;Fauque et al, 2007;Saenz-de-Juano et al, 2016). It has been shown that in patients belonging to either high or low strata of antimüllerian hormone (AMH) concentration an inverse correlation exists between the daily dose of recombinant human follicle stimulating hormone (rhFSH) used in the stimulation and the proportion of blastocyst formation (Arce et al, 2014).…”
Section: Effects Of Ovarian Stimulation On Embryology Parametersmentioning
confidence: 99%
“…Aggressive ovarian stimulation has effects on the patient's wellbeing, by increasing the risk of ovarian hyperstimulation syndrome (OHSS) (Delvigne, 2009;Rizk, 2009), as well as on the endometrium and the ovaries. There are studies showing an increased likelihood of embryo aneuploidy in connection with aggressive ovarian stimulation, even in patients younger than 35, including post-zygotic segregation errors and maternal segregation errors (Baart et al, 2007;Haaf et al, 2009), as well as having a negative impact on the maintenance of genomic imprints during early embryogenesis (Denomme and Mann, 2012;Fauque et al, 2007;Saenz-de-Juano et al, 2016). It has been shown that in patients belonging to either high or low strata of antimüllerian hormone (AMH) concentration an inverse correlation exists between the daily dose of recombinant human follicle stimulating hormone (rhFSH) used in the stimulation and the proportion of blastocyst formation (Arce et al, 2014).…”
Section: Effects Of Ovarian Stimulation On Embryology Parametersmentioning
confidence: 99%
“…The effect of ovulation induction directly affects the quality of the oocytes obtained, which then affects the clinical outcome of the whole assisted pregnancy therapy. COH includes the processes of follicular recruitment, development, and ovulation, which are usually not completely synchronized [18] . Only by overcoming the factors of nonsynchronization is it possible to obtain high-quality oocytes of the same quality as the dominant follicles in the natural cycle.…”
Section: Discussionmentioning
confidence: 99%
“…A recent paper reported the successful production of offspring in mouse infertile model following transplantation of primordial follicles within artificial biomaterial grafts [54]. Several investigators are studying whether deleterious epigenetic events occur in cultured follicles [55,56].…”
Section: • • In Vitro Growth and Maturation Of Folliclesmentioning
confidence: 99%